(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2010)
After forty years from its discovery, the history of the field surveys and of the researches on the fossiliferous deposits on Gargano is briefly reported. The Gargano fauna belongs to the Abruzzo-Apulian Palaeobioprovince (including also Scontrone and Palena, Abruzzo). The fossil assemblage comprehends all the classes of terrestrial vertebrates: Reptilia, Amphibia, Aves and Mammalia. The faunal composition is unbalanced and presents the features of a typical insular endemic fauna. The bulk of the assemblage is composed of small mammals and birds. Based on literature, we report the most characteristic features, phylogenetic relationships, and evolutionary remarks on a list of mammals, focusing particularly on the adaptations of the most endemic taxa. Moreover, a biochronological scheme of the major faunal events is proposed and illustrated. Although still imperfect, the scheme is the first synopsis of all the biochronological and taxonomical information on mammals so far available. Eventually, the hypotheses on the origin and modes of colonisation are summarized and shortly discussed. From this overview the Gargano fauna is indeed of great interest for studies of evolution and biogeography. Nonetheless, there are persistent uncertainties on its age and origin, as well as on the age of infilling of the karstic fissure system of this unique fossiliferous locality.